Penggunaan Smartphone Dalam Pembelajaran Di Madrasah Ibtidaiyah Mathlaul Anwar Tegal Waru Ciampea Bogor - Ari, Ari; Iswandi, Irvan (JUPE : Jurnal Pendidikan Mandala, 2023)
There are actually a lot of learning support sources everywhere, not just in books or in magazines, even in the current era of advanced technology, we can easily get learning support resources through smartphones, in smartphones, both in use as learning supports or as a means to make it easier to communicate. It's different with books that can only be found in libraries or bookstores, and even then there are still many students who complain because it's hard to find the book they want. The purpose of this study was to find out the use and constraints of use, as well as find out the advantages and disadvantages of using smartphones by students in learning at Madrasah Ibtidaiyah Mathlaul Anwar Tegal Waru Ciampea Bogor. The research method used in this study is a qualitative approach. The use of smartphones in Madrasah Ibtidaiyah Mathlaul Anwar Tegal Waru Ciampea Bogor has been used as a companion to student learning resources during class hours, both online and face-to-face. The obstacle faced is a slow WiFi network. These deficiencies and obstacles can be overcome by teachers and students. As for some of the benefits students get when using smartphones include being a learning resource, easy to understand the material presented and can be completed quickly, students look more enthusiastic in learning, raises competition among students, because students are more active. It's easier to get information.